Analysis of bacterial contamination and antibiotic residue of beef meat from city slaughterhouses in East Java Province, Indonesia - Soepranianondo, Koesnoto (Vet World, 2019)
AIM: This research aimed to analyze the presence of microbial contamination and antibiotic residue in beef meat from city slaughterhouses in East Java Province, Indonesia. MATERIALS AND METHODS: A total of 40 samples from city slaughterhouses were used in this study. The tests for microbial contamination used several methods including total plate count (TPC), most probable number of Escherichia coli, detection of Staphylococcus aureus using Mannitol Salt Agar media, Salmonella spp. detection using Bismuth Sulfite Agar media and Triple Sugar Iron Agar media, and detection of the antibiotic residue by screening tests. RESULTS: Most of the samples were contaminated with E. coli (32.5% positive samples) and S. aureus (20.0% positive samples). The mean values of TPC and S. aureus contamination were lower than the maximum limit of contamination, which were 41.58 CFU/g and 13.93 CFU/g, respectively, while the mean value of E. coli contamination was 27.03 CFU/g which was higher than the maximum limit. A low frequency of TPC (5% positive samples) and Salmonella spp. contamination (2.5% positive samples) was found in meat samples. Meat samples from two of the surveyed slaughterhouses were tested positive for antibiotic residue and six of the 40 samples (15%) were also tested positive for the antibiotic residue. CONCLUSION: It was concluded that most of the microbial contamination in beef meat from city slaughterhouses was below the maximum limit of contamination and only two slaughterhouses were found antibiotic residues in the meat samples.